AI in the news: reshaping the information ecosystem? - Simon, FM; Isaza-Ibarra, LF (Oxford Internet Institute, University of Oxford, 2023)

(untitled)
Journalism faces a decline of traditional business models. News leaders are increasingly pressured to reorient toward data-driven logics. Many news organisations now bet big on AI investments, hoping that the technology can generate additional revenue or free up staff time. But problems emerge: Some journalists fear being replaced with AI; there are possible frictions between journalistic values and the values encoded into AI systems and infrastructures; and little is known about the impact of AI on the news and the health of our public discourse. AI also poses the risk of making news organisations even more reliant on the technology and platforms companies that dominate in AI development – potentially aggravating the economic problems that news organisations face. Starting in March 2021, the project ‘AI in the News: Reshaping our Information Ecosystem’1 at the Oxford Internet Institute investigated these and related questions, generously funded by Oxford University’s Research Centre in the Humanities (TORCH) and the Minderoo- Oxford Challenge Fund in AI Governance and with administrative support from the Oxford Internet Institute and Balliol College. The aim of the project, led by Felix M. Simon and co-launched by Prof Gina Neff, was to identify key issues in this space, collect evidence, and start a conversation among academic and industry leaders about those issues. These efforts culminated in a public symposium held at Balliol College on 25th May 2023, which sought to foster discussions between industry experts, academics, and students on the key issues identified during the active research phase.2 The symposium featured three panel discussions on ‘AI in the Workplace’, ‘AI, News, and the Role of the Technology Sector’, and ‘AI and the Implications for Public Discourse’. Held under the Chatham House Rule, participants included leading experts on AI and the news, including Shreya Vaidyanathan, Product Manager at Bloomberg LP; Jane Barrett, Global Editor for Media News Strategy at Reuters; Siddharth Venkataramakrishnan, Banking and Fintech Correspondent at the Financial Times; Melissa Heikkilä, Senior Reporter for AI at MIT Technology Review; Nic Newman, Senior Research Associate at the Reuters Institute for the Study of Journalism; David Caswell, Executive Product Manager at the BBC; and Tom Standage, Deputy Editor at The Economist. The diverse audience comprised journalists, policy experts, technology specialists, and students from the University of Oxford and beyond, contributing to a rich and multifaceted exchange of ideas. This report provides a summary of the main themes that emerged during the symposium and outlines a few recommendations as well as blind spots to be addressed in future research. It examines the role AI plays in news production and distribution and, consequently, in the broader public sphere drawing from the experiences of various well-known British and US-American news organisations. We begin by summarising what media organisations understand AI to be and how AI tools are increasingly being integrated into all stages of the process of news creation and distribution. Notably, different news organisations have varying degrees of engagement with AI. Some have been using AI for years and have developed their own tools, while others are still exploring these technologies. Next, we summarise what was discussed in the three panels of the symposium. First, we provide an overview of the tensions and issues emerging from AI’s use in new organisations and how the organisations have navigated the same. The discussion showed that maintaining reliability and trustworthiness was a guiding principle for many. For the second panel, participants discussed the possible dependency on the providers of AI tools and systems, especially major technology companies. They recognised the influence that these companies already have and some of them, though not all, expressed their concern that AI could increase their power even further. In the final section of the symposium, the speakers talked about the long-term implications of AI for the industry and the broader public sphere. We conclude this report by presenting some recommendations around the use of AI in the news and highlighting some of the blind spots of the current discussions on this topic.